MoPMIT : a prototype system for reactive maintenance projects in The UK - Ali, Kherun Nita; Sun, Ming; Gary J., Petley; Peter S., Barrett; Kagioglou, Mike (Faculty of Built Environment, UTM, 2004)
More Productive Minor Construction Project through Information Technology (MoPMIT) is a research project that focuses the use of IT to improve the management of reactive maintenance (RM) works for large clients. The research participants include a group of building owners, facilities management team, contractors and suppliers. At the early stage of this research, several existing deficiencies with RM projects were identified, which require some measures of improvement. These problems include poor communication between different parties; lack of knowledge sharing; and poor quality of information, which often lead to longer time taken to fix a problem and incurs higher cost. The current development of knowledge management and Internet technology has offered a platform for developing an online knowledge management system to improve the operation of these RM projects. A prototype web-based system called â€œMoPMITâ€? has been developed to demonstrate the idea by having all parties in the process to share information and communicate on a common interface with pre-allocated password access as a control mechanism that will limit each user to its role in the RM process. Testing has been conducted and feedbacks from potential MoPMIT users show that there is a consensus that the system will lead to better management of knowledge, improve communication and better data sharing among all parties. This paper will illustrate how the system operates and the theoretical underpinning that has enabled the development of the tool.